(untitled) (Intent Research Scientific Journal, 2023)
The aim of our study was to evaluate the effectiveness of our method of complex pathogenetic treatment of chronic catarrhal gingivitis in 97 patients who were examined at the Department of Hospital Therapeutic Dentistry of the Polyclinic of the Tashkent State Dental Institute. Taken into account that there is a large arsenal of medicinal agents, however, there are no optimal methods for influencing the mechanism of development of inflammatory periodontal diseases in the pathology of the hepatobiliary system (HBS), therefore, the problem of treating chronic generalized catarrhal gingivitis (CGCG) in this pathology is still relevant. Our study was conducted with the aim to study the effectiveness of irrigation of the gums with Parodontax rinsing device with Waterpik WP apparatus for the pathology of the hepatobiliary system. After the completion of the complex pathogenetic treatment using the irrigation of the gums with Parodontax with the Waterpik WP apparatus, high results were obtained, in which the anti-inflammatory efficiency was defined as a reduction of the PMA index. The PMA value decreased from 22.16 ± 1.64% to 5.65 ± 0.05%, the OHI-s index decreased from 2.31 ± 0.22 to 0.19 ± 0.27; SBI 2.14 ± 0.11 decreased and amounted to 0.14 ± 0.11. Thus, the effectiveness of complex pathogenetic treatment and local application of irrigation of the gums of the Parodontax rinser with the WaterpikWP apparatus is confirmed by the results of clinical and biochemical studies.